Nisei Memories : My Parents Talk about the War Years - Takemoto, Kenneth Kaname (Book collections on Project MUSE., 2006)
"Like so many others, Ken and Alice had never spoken of their experiences, which, as their son explains, "loomed as backdrops to our lives, but until now were never discussed." While his father had relived his wartime experiences over and over in his mind, his mother blocked many of hers from memory. Takemoto fills in some of the gaps with information gleaned from correspondence and documents. Of unusual power and appeal, the interviews lead readers through the half century of uncertainty and trauma endured by the family before it was able to confront issues central to its existence. They tell a story of perseverance and forgiveness and, ultimately, pride."--Jacket.